2016
DOI: 10.1080/02688697.2016.1208810
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of pelvic girdle pain with dorsal root ganglion stimulation

Abstract: The authors report the first case of successful implantation of a dorsal root ganglion stimulator at L1 and L2 for sustained improvement in chronic pelvic girdle pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 3 publications
1
26
0
2
Order By: Relevance
“…Morgalla et al reported 63.5% overall pain relief and improvement in BPI scores under DRGS in patients with post-herniorraphy inguinal pain, which was sustained even after three years of observation (14). These successful rates of pain relief have been replicated in other more recent smaller case series (11,55,56) as well as in some case reports (13,16,18,19,26). In our study, we had 74% mean pain reduction at one month and 70% at six-month postsurgery.…”
Section: Drg Stimulationsupporting
confidence: 76%
See 1 more Smart Citation
“…Morgalla et al reported 63.5% overall pain relief and improvement in BPI scores under DRGS in patients with post-herniorraphy inguinal pain, which was sustained even after three years of observation (14). These successful rates of pain relief have been replicated in other more recent smaller case series (11,55,56) as well as in some case reports (13,16,18,19,26). In our study, we had 74% mean pain reduction at one month and 70% at six-month postsurgery.…”
Section: Drg Stimulationsupporting
confidence: 76%
“…In 2011, dorsal root ganglion stimulation (DRGS) was introduced for the treatment of NP (9). Since then, numerous publications have shown positive clinical results using DRGS for chronic NP (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Rowland et al describe a case of intractable pelvic girdle pain successfully treated with DRGS. The patient was 37‐year‐old woman with a 9 year history of chronic pain which had left her heavily medicated and bed bound.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical stimulation of the DRG can reduce neuronal excitability and the idea that dorsal root ganglion stimulation (DRGS) may be directly treating pathological neurons makes it an alluring target. To date DRGS has been used to treat postherpetic neuralgia , phantom limb pain (PLP) , failed back surgery syndrome (FBSS) post herniorrhaphy groin pain , radicular pain , complex regional pain syndrome (CRPS) of the foot , knee and distal upper limb , postsurgical perineal pain , pelvic girdle pain , peripheral nerve injury following kidney surgery , pain following femoral vascular access , and pain following deep vein thrombosis (DVT) amongst other unpublished indications.…”
Section: Introductionmentioning
confidence: 99%
“…published the results of a case series using stimulation at the conus in one patient and mid‐thoracic (T5–7) in four others . Most recently, Rowland et al published a case report on a 37‐year‐old female with CPP (girdle pain) successfully treated with DRGS—leads were placed at L1 and L2 . While there is no evidence to support why the use of SCS for CPP has not experienced more widespread adoption, the lack of agreement on where one should target has likely done little to instill confidence on would‐be users and should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%